2012
DOI: 10.1038/ejhg.2012.4
|View full text |Cite
|
Sign up to set email alerts
|

A large-sample assessment of possible association between ischaemic stroke and rs12188950 in the PDE4D gene

Abstract: Previous reports have shown ambiguous findings regarding the possible associations between ischaemic stroke (IS) and single nucleotide polymorphisms (SNPs) in the phosphodiesterase 4D (PDE4D) gene region. The SNP rs12188950 (or SNP45) has often been studied in this context. We performed a multi-centre study involving a large sample of 2599 IS patients and 2093 control subjects from the south and west regions of Sweden to replicate previous studies regarding IS risk and rs12188950. Subjects from Lund Stroke Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
0
10
1
Order By: Relevance
“…Metabolic and cardiovascular manifestations, including hypertension, have also been reported 20. In addition, genome-wide association studies have suggested PDE4D as a candidate gene in ischaemic stroke 21. One acrodysostosis patient in our study suffers from severe hypertension requiring medication, one has diabetes type 1 and another patient has been investigated for suspected deep vein thrombosis (table 3).…”
Section: Discussionmentioning
confidence: 54%
“…Metabolic and cardiovascular manifestations, including hypertension, have also been reported 20. In addition, genome-wide association studies have suggested PDE4D as a candidate gene in ischaemic stroke 21. One acrodysostosis patient in our study suffers from severe hypertension requiring medication, one has diabetes type 1 and another patient has been investigated for suspected deep vein thrombosis (table 3).…”
Section: Discussionmentioning
confidence: 54%
“…We included 3986 patients with IS and 2459 control subjects from three Swedish hospital centers: Lund Stroke Register (LSR), Malm€ o Diet and Cancer Study (MDC) and the Sahlgrenska Academy Study on Ischaemic Stroke (SAHLSIS) [10,11,[21][22][23][24][25][26][27].…”
Section: Study Populationmentioning
confidence: 99%
“…However, there are relatively limited studies on this association. A study by Liao et al (2010) demonstrated that there was a significant association between rs12188950 and ischemic stroke, but no such correlation was found in a large sample population study conducted in Sweden (Lovkvist et al, 2012). The rs12188950 polymorphism in PDE4D has been shown to be a protective factor for ischemic stroke in other populations (Lovkvist et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the rs12188950 polymorphism did not exist in the current study population. A study of Caucasians and African-Americans in the US also has shown that there was no polymorphism of rs12188950 (Lovkvist et al, 2012). Recently, a study on hospitalized Chinese patients was conducted, and the authors concluded that the rs918592 polymorphism was significantly associated with ischemic stroke (Song et al, 2012).…”
Section: Discussionmentioning
confidence: 99%